(untitled) (Jurnal Ilmu Gizi dan Dietetik, 2026)
Early adolescence represents a critical developmental stage marked by heightened vulnerability to nutritional disorders, which are influenced by social influences and lifestyle behaviors that may hinder optimal health. Within the jurisdiction of Pasundan, Bandung, the prevalence of adolescent obesity is notably high. One contributing factor that may affect physical activity levels and nutritional status is the influence of subjective norms and behavioral intentions. This study aims to investigate the associations between subjective norms, intentions toward physical activity, actual physical activity behavior, and nutritional status among early adolescents. This study employed a quantitative design with a cross-sectional approach, involving 64 students were selected using the Lemeshow sampling formula. Bivariate analysis using the Fisher’s Exact test identified a significant between subjective norms and physical activity intentions (p=0,001). However, no significant relationships were observed between intentions and physical activity (p=0,187), subjective norms and actual physical activity (p=0,385), between intentions and nutritional status (p=908), or between subjective norms and nutritional status (p=0,535). These findings indicate that while subjective norms may shape intention, they are insufficient on their own to influence tangible behavioral changes in adolescents.